PENGARUH VIRALNYA KEJAHATAN DI MEDIA SOSIAL TERHADAP PENEGAKAN HUKUM PIDANA DILIHAT DARI ASAS EQUALITY BEFORE THE LAW - Muhammad Fikri; Erdianto Erdianto; Davit Rahmadhan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
Crimes that go viral on social media have an impact on law enforcement, many crimecases that go viral on social media are starting to be highlighted by law enforcement, the lackof response by law enforcement to viral cases makes the public angry so that the lack of a senseof justice that people feel causes hashtags to appear.#noviralnojustice, for example the victimof a robbery who is made a suspect for killing a robber, this is clearly not in accordance withArticle 49 Paragraph (1) Number 1 of 1946 of the Criminal Code, he should not be made asuspect for reasons of justification, the act of defense is forced for himself or others. Then thepolice who do not take reports seriously, this is not in accordance with the duties andauthorities of the police in Article 13 of Law Number 2 of 2002 concerning Main Duties of theIndonesian National Police. Therefore, the purpose of this thesis research is first, to determinethe influence of social media on law enforcement in Indonesia associated with the principleequality before the law. Second, to find out the law enforcement of the viral case seen from theside of justice.This type of research can be classified into the type of normative legal research. In thistype of legal research, law is often conceptualized as what is written in laws and regulationsor law is conceptualized as rules or norms which are benchmarks for human behavior that areconsidered appropriate. Therefore, the first data source is only secondary data, which consistsof primary legal materials, secondary legal materials, and tertiary data.From the results of this study, the first result was obtained, namely, the existence of socialmedia in the community greatly influences law enforcement, because law enforcement officials,both police investigators, public prosecutors, judges, in carrying out law enforcement havecaused uproar that is felt in society, especially the issue of justice, because in cases of robbery,the police do not see any justification in Article 49 Paragraph (1) of Law Number 1 of 1946which law enforcers are supposed to be fair in providing legal clarity to the public, just theopposite. With social media, the public can monitor the proper law enforcement process.Second, justice is an ideal value that humans always strive for, but in reality, achieving justiceas an ideal value is very complex and never complete, in a rule of law country like Indonesia,efforts to achieve justice are very important and should not be ignored. The influence of justiceon law enforcement has an important role. However, in reality, Indonesian people tend to usesocial media as a means to encourage faster and fairer law enforcement.Keywords: Crime, Social Media,Asas Equality Before The Law